Problem-Based Learning to Metacognition in Physics Learning in Indonesia: Literature Review - Sri Wahyu Widyaningsih; Dedi Kuswandi; Fikri Aulia; Andista Candra Yusro; Irfan Yusuf (Universitas Lambung Mangkurat, 2024)
Physics learning encountered a hurdle due to students' insufficient metacognitive abilities, emphasizing the need to improve their understanding of learning and problem-solving procedures. This literature review aimed to explain the results of applying Problem-Based Learning (PBL) to metacognition in physics learning in Indonesia. This literature review was sourced from scholarly articles published between 2013-2023, retrieved via Google Scholar using tools like Publish or Perish and Open Knowledge Map. The search utilized keywords such as “Pembelajaran Berbasis Masalah” or “Problem-Based Learning” and “Metacogni*” and “physics”. These criteria included relevance to PBL in physics learning, metacognitive, publication in reputable journals, and full-text availability. From the initial pool of 214 articles, a selection process was applied based on the literature review criteria, including 11 national and one international article. Based on the findings of the literature review analysis, it was discovered that there was limited research on the application of PBL to metacognition in physics education in Indonesia, indicating a need for further exploration. Of the 12 articles examined, only 2 (16.7%) focused on developing PBL tools to facilitate metacognition, ensuring validity, practicality, and effectiveness in enhancing learner metacognition. Additionally, 6 of the 12 articles (50.0%) suggested that implementing the PBL model in physics education improved metacognitive abilities. However, 4 of the 12 articles (33.3%) reported no significant impact on enhancing metacognition through PBL learning methodologies. The results of this study indicated a complex correlation between PBL and the advancement of metacognitive skills in physics education. This underscored the significance of further research to pinpoint the factors influencing these outcomes and to refine PBL instructional approaches.